Effect of decrease in radial inclination of distal radius fractures on distal radioulnar joint stability: a biomechanical study. (November 2018) - Bessho, Yuki; Nakamura, Toshiyasu; Nishiwaki, Masao; Nagura, Takeo; Matsumoto, Morio; Nakamura, Masaya; Sato, Kazuki
We investigated the relationship between the radial inclination of the distal radius and distal radioulnar joint stability. Six fresh-frozen upper extremities were used. Radial inclination was decreased by 10° and 20° and increased by 10° from the original radial inclination. Distal radioulnar joint stiffness was assessed with an intact radioulnar ligament and after partial and then complete sectioning of the radioulnar ligament. Radial angulation deformities significantly increased distal radioulnar joint stiffness when the radioulnar ligament is totally or partially attached to the ulnar fovea. After complete sectioning of the radioulnar ligament, distal radioulnar joint stiffness decreased significantly; additional radial angulation deformity slightly increased distal radioulnar joint stiffness, but the distal radioulnar joint never recovered to the original stiffness. Based on the results, radial angulation deformities of the distal radius should be corrected within 10° when the radioulnar ligament is intact, to reduce the risk of symptomatic distal radioulnar joint instability.